Jüdisches Leben - Ehmann, Annegret; Heid, Ludger 1945-; Kampe, Norbert 1948-; Landwehr, Rolf 1942-; Dreßen, Wolfgang 1942- Hrsg; Friedlander, Albert H. 1927-2004; Museumspädagogischer Dienst Berlin (Berliner Topografien, 1985)
Jüdisches Leben in Berlin